Searched refs:biasedTailExponent (Results 1 – 2 of 2) sorted by relevance
44 const int biasedTailExponent = (int)(lobits.x >> 52) & 0x7ff; in __fixtfdi() local49 (unbiasedHeadExponent - (biasedTailExponent - (1023 - 10))); in __fixtfdi()84 const int biasedTailExponent = (int)(lobits.x >> 52) & 0x7ff; in __fixtfdi() local85 tailMantissa >>= 1075 - biasedTailExponent; in __fixtfdi()
38 const int biasedTailExponent = (int)(lobits.x >> 52) & 0x7ff; in __fixunstfdi() local43 (unbiasedHeadExponent - (biasedTailExponent - (1023 - 11))); in __fixunstfdi()